Roadmap to DILI research in Europe. A proposal from COST action ProEuroDILINet - M.I. Lucena; M. Villanueva-Paz; I. Alvarez-Alvarez; G.P. Aithal; E.S. Björnsson; G. Cakan-Akdogan; F.J. Cubero; F. Esteves; J.M. Falcon-Perez; B. Fromenty; C. Garcia-Ruiz; J.I. Grove; et al. (Pharmacological Research, 2024)
In the current article the aims for a constructive way forward in Drug-Induced Liver Injury (DILI) are to highlight the most important priorities in research and clinical science, therefore supporting a more informed, focused, and better funded future for European DILI research. This Roadmap aims to identify key challenges, define a shared vision across all stakeholders for the opportunities to overcome these challenges and propose a high-quality research program to achieve progress on the prediction, prevention, diagnosis and management of this condition and impact on healthcare practice in the field of DILI. This will involve 1. Creation of a database encompassing optimised case report form for prospectively identified DILI cases with well-characterised controls with competing diagnoses, biological samples, and imaging data; 2. Establishing of preclinical models to improve the assessment and prediction of hepatotoxicity in humans to guide future drug safety testing; 3. Emphasis on implementation science and 4. Enhanced collaboration between drug-developers, clinicians and regulatory scientists. This proposed operational framework will advance DILI research and may bring together basic, applied, translational and clinical research in DILI.